Psychiatrists as forensic authorities: evaluation of dangerous habitual offenders in West Germany during the 1960s – the Helmut Hoinka case - Kosenko, Oxana; Skuban-Eiseler, Tobias; Steger, Florian (Frontiers in Psychiatry, 2024)
Preventive detention for highly dangerous habitual offenders has been in force in Germany for 90 years. The necessity of this measure is hotly debated from a legal perspective. However, the assignment of preventive detention is largely determined by the opinion of medical experts. This article discusses the role of medical experts and the issues they face in evaluating the dangerousness of habitual offenders using the case of the marriage swindler Helmut Hoinka, prosecuted several times in the Federal Republic of Germany in the 1960s. The medical experts who evaluated Hoinka were aware of the defendant's criminal record prior to the evaluation, which was a source of bias. In addition, the criteria for classifying the offender as a dangerous habitual offender were open to a wide range of interpretations. Hoinka's high level of intelligence was negatively emphasized. Some test results were considered unreliable because it was assumed that Hoinka had manipulated his answers. Personal value judgments were allowed in assessing Hoinka's personality. Hoinka's criminal behavior was considered a medical symptom of psychopathy because it violated general moral and social norms. The medical reports of both experts showed that the psychiatrists believed in the genetic nature of psychopathy and criminal behavior. Their criminological prognosis was fully supported by the court in imposing the sentence.Challenges to Hoinka's criminological prognosis were the experts' personal biases, their belief in the theory of genetic predisposition to crime, the lack of clear criteria for antisocial personality disorder, and the absence of forensic recommendations for "psychopathic" criminals. The experts' opinion on Hoinka's criminal predisposition was crucial to the imposition of the sentence.